Civil society in East Asian countries: contributions to democracy, peace and sustainable development: proceedings of the conference - Didvalis, Linas (editor) (Vytautas Magnus University, 2018)
This publication is dedicated to research on East Asian civil society with special attention given to composition, development and activities of non-governmental sector. The publication gathers research of authors from Lithuania, Germany, UK, South Korea and the Czech Republic who analyze not only general situation in East Asia but also provide detailed case studies. This allows to learn more about political and socioeconomic circumstances that determine particular characteristics of civil society in China, Korea and Japan. The collection of articles will be useful both for specialists of East Asia and researchers coming from the fields of political science, history, sociology and anthropology who would like to know more about familiar topics, such as labor movements, environmental organizations or democratization processes, in the context of less known countries.